An experimental and numerical study of corrosion distribution dependent bond–slip relationship of reinforced concrete. (December 2022) - Yu, Ai-Ping; Zhao, Yan-Lin; K.C., Diwakar; Naqvi, Mohammad Wasif; Hu, Liang-Bo
Abstract: Corrosion of reinforcing steel plays an important role in the performance of reinforced concrete. The distribution of the corrosion damage along the rebar may have a significant influence on the bond–slip relationship of the reinforced concrete but has yet to be extensively investigated. The present study aims to explore a quantitative approach to establishing a bond–slip model that addresses the influence of localized corrosion damage. Experimental results of controlled, accelerated corrosion tests and subsequent pull-out strength tests are used to quantify the corrosion damage distribution and compute the bond stresses and slip displacements along the rebar, respectively. A model of reinforced concrete bond–slip relationship is developed after a function for the distribution of the normalized bond stress along the normalized location of the rebar is established. Calibration of involved modeling parameters are made for both uncorroded and corroded reinforced concretes based on the presented experimental results. The present study shows promising potential for the consideration of corrosion distribution in the development of suitable mathematical models for corroded reinforced concrete.